Pentingnya Penggunaan Bahasa Indonesia di Lingkungan Sekolah SMK Negeri 3 Kota Bengkulu - Rahayu Rezeki; Intan Saputri; Rizki Iftitah Rahmat (Education and Talent Development Center Indonesia, 2026)
In daily life, of course, every community in Indonesia has its own language in the process of interacting between one community and another. In this process, the application of the Indonesian language which absolutely should be used by every community. Moving on from this, the use of Indonesian in the school environment must be echoed, because as an educated person must be able and fluent in Indonesian. The formulation of the problem in the service activities carried out by the author at SMK Negeri 3 Bengkulu City is that there are many students in the school environment who are not fluent in Indonesian and in the process of interaction they mostly use regional languages both in the learning process and non-learning. Therefore, the purpose of carrying out this service activity is to intensify the use of good and correct Indonesian language in the school environment, especially in the school environment of SMK Negeri 3 Bengkul City